2020
DOI: 10.26434/chemrxiv.12657230.v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapidly Reversible Organic Crystalline Switch for Conversion of Heat into Mechanical Energy

Abstract: <div> <div> <div> <p>Solid state thermosalience—a sudden exertion of an expansive or contractive physical force following a temperature change in a solid state compound—is rare, few are reversible systems, and most of these are limited to a dozen or so cycles before the crystal degrades or they reverse slowly over the course of many minutes or even hours. In this work, we show a fully reversible actuator that is stable at room temperature for multiple years and is capable of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previously, cooperative transition mechanisms have typically involved rotational 7,11,21 or sliding motion within the crystal system. 19,23,26 In organic molecules, this motion has been facilitated by the side chains of the molecules which have been shown to go through a rotational order−disorder 11,27 transition or undergo a conformation change in the case of alkyl chains. 28 In our recent work, 28,29 we observed that 2DQTT-C 8 C 10 undergoes two thermally accessible polymorph transitions: the I−II (cooperative) and II−III (nucleation and growth) transitions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, cooperative transition mechanisms have typically involved rotational 7,11,21 or sliding motion within the crystal system. 19,23,26 In organic molecules, this motion has been facilitated by the side chains of the molecules which have been shown to go through a rotational order−disorder 11,27 transition or undergo a conformation change in the case of alkyl chains. 28 In our recent work, 28,29 we observed that 2DQTT-C 8 C 10 undergoes two thermally accessible polymorph transitions: the I−II (cooperative) and II−III (nucleation and growth) transitions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Typically, nucleation and growth transitions exhibit large changes in molecular packing and slow kinetics, 14 making it promising for the kinetic stabilization of a particular metastable polymorph. Cooperativity, on the other hand, exhibits rapid transition kinetics 9,23,24 and low energy barriers 8,25 and is coupled with intriguing mechanical properties, 7,11,23 offering pathways to novel, reversible switching devices. By controlling the presence of these transitions, we may provide a method of rationally designing new switching devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Light-and heat-induced phase changes can result in crystal actuation, 8 such as bending, 9,10 jumping, 7,11,12 and expansion. 13,14 Early studies regarding vapochromism or reversible color changes driven by vapor absorption and desorption were based on organometallic complexes, but in recent years, organic crystals that exhibit vapochromism have been reported. 15−17 These new achievements in molecular crystal chemistry are complementary to the concept of crystal engineering, 18 aimed at understanding molecular interactions and designing new crystalline materials with desired physical and chemical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fig.6| Comparison of working temperatures of reported systems and actuation device of 1. a Response temperature deviating from room temperature of reported thermosalient molecular crystals. NBFB 39 ,[7]Helquat salt47 , TIP-P19 , HMB48 , 6-CAN49 , ditBu-BTBT19 , TPA17 , NDI derivant50 , DABCO(CZ) 2 51 , TBB52 , GN53 , [Ni II (en) 3 ] (ox)54 , [Co(NO 3 ) 2 (L)]55 , ABN40 , TCB18 . T tr and RT represent phase transition temperature and room temperature of 293 K, respectively.…”
mentioning
confidence: 99%